KORELASI KERUSAKAN BATUAN PENYUSUN CANDI TERHADAP STABILITAS BANGUNAN BERDASARKAN SIFAT FISIS DAN MEKANIS - , IRAWATI BUDI RESPATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Prambanan temple is a cultural sanctuary and included into a list world heritages, so the existence is necessary to preserve. Geologically, the temple is on the active fault. The 5,9 SR earthquake caused severe damages on the complex of Prambanan temple. The damages are both in structure and materials with various types and conditions of damage. This study is focused on the composing stones of Shiva temple as a main temple in the complex of Prambanan temple. The objective of the study is to find out a correlation between damages of the composing stones and the stability of building based on the technical and mechanical properties. In the study, a testing was done in both laboratory and field using Uniaxial Test, Brazilian Test, Index Properties, Permeability Test, Shear Stress Test, and Schmidt Hammer Test type L to find out the characteristics of stones. In addition, analysis of stability in the structure of Siva temple was based on element method using Plaxis software version 8.6. Soil and structure of the temple was modeled using the 2D axysimmetry and mohr-coulomb, where the materials had collapse. The structure of the temple was viewed in three conditions, i.e. those of complete temple (no fracture), of fractured temple without the effect of interface and of fractured temple with the effect of interface. The load was spread evenly for 5 kN/m2 and 50 kN/m2 in the yard of the temple, and variation in earthquake was simulated to find out the stability of the templeâs structure. Result of the correlation with values of Schmidt Hammer and UCS shown the equation, i.e. UCS = 0.027Rn2 + 0.662Rn â 3.558 with a correlation coefficient (R2) of 0.903, where minimal values of Schmidt Hammer used 10. From the correlaction graphic, it can be said that the highest values of UCS was in red andesite stone, where the value of UCS for black andesite stone was Â½ of the value of UCS for the red andesite stone, while that of tuff was 1 ôµ3 of the value of UCS for the red andesite stone. The simulation by using the 2D approach done in three conditions of the templeâs sctructure, where load was evenly given in the yard and variation in earthquake. The presence of fracture and interfaces effect the structural stability on the temple. Shiva temple structure is still able to receive earthquake load with load conditions due to the presence of fracture earthquake in 2006, which is indicate by the increase in displacement is not too significant and the decrease in shear stress accurs.